How to create alternating series with happening every two terms

I’m looking for a technique for creating alternating negatives and positives in a series. Specifically: when n=1, the answer is +, n=2 is +, n=3 is -, n=4 is -… etc.

I have every other part of the series written but I can’t figure out that last piece… here’s what I have now:

$$\sum_1^\infty 2^{n-1}(1^n+(-1)^n)/(3^{n-1}n!)*x^n$$

Technically, every other term is 0 so there doesn’t really need to be two negatives in a row, it just has to sync up where I need them–I’m just guessing that I’d need it to work that way. Thanks for your assistance!

Solutions Collecting From Web of "How to create alternating series with happening every two terms"

Here’s a little trick which you might appreciate, or which you might find to obfuscate the matter. The triangular numbers $1,3,6,10,15,\dots$, given by the formula $T_n=n(n+1)/2$, have the property that $T_{4k+1}$ and $T_{4k+2}$ are odd and that $T_{4k+3}$ and $T_{4k+4}$ are even. So the expression $-(-1)^{T_n}=(-1)^{T_n+1} = (-1)^{(n^2+n+2)/2}$ alternates in sign in the way that you are looking for. In other words, if your original series is $\sum_{n=1}^\infty a_n$, where all $a_n$ are positive, then the modified alternating series you want is
$$
\sum_{n=1}^\infty (-1)^{(n^2+n+2)/2}a_n.
$$

$$S=\sum^\infty_{n=1}(-1)^{n+1}f(2n-1)+\sum^\infty_{n=1}(-1)^{n+1}f(2n)=f(1)+f(2)-f(3)-f(4)+…$$

$$ \sqrt 2 \; \sin \left( \frac{(2n-1)\pi}{4} \right) $$

Try: $$a_n = (-1)^{\frac{\left(2n+1+(-1)^{n+1}\right)}{4}+1}$$

Then, $$\langle a_n\rangle = 1, 1, -1, -1, 1, 1, \ldots$$

Derivation:
“Any sufficiently advanced technology is indistinguishable from magic.” – Clark’s Third Law
I don’t really know how to describe how I got that… ;)

I must confess that I do not see the relation between your interesting questions and the expression you give. In practice,$$\sum_1^\infty 2^{n-1}(1^n+(-1)^n)/(3^{n-1}n!)*x^n=3 \left(\cosh \left(\frac{2 x}{3}\right)-1\right)$$ just involves even powers of $x$.